Poverty in The Informal Sector: A Case Study at West Nusa Tenggara Province - Miftahul Surur; M. Pudjihardjo; Wildan Syafitri (Journal of International Conference Proceedings, 2022)
This study will try to see the impact of the dominance of the informal sector in West Nusa Tenggara Province which reaches 73.89% of the workforce when compared to the formal sector which is only 26.11%. While the HDI level of this province is 29th out of 34 provinces throughout Indonesia, the main reason is that the majority of the population who enter the informal sector have a low level of education and do not even go to school. It is very important to analyze the factors that influence the poverty of actors in the informal sector, especially in the West Nusa Tenggara Province, and to find out what variables affect poverty in the informal sector. Based on the results of research using Susenas data in 2021, it was found that the variables of education, marital status, number of family members, informal activities, use of technology, social security, access to capital, and migration status had a significant effect on poverty in the informal sector, only the domicile location variable did not significantly effect on poverty in the informal sector at West Nusa Tenggara Province.Â Keywords: Poverty, Informal Sector, Education, Technology, Gender